Subcritical water extraction of dandelion (Taraxacum officinale L.) flowers: Influence of temperature on polyphenols content and antioxidant activity - Brezo-Borjan Tanja Ž.; Švarc-Gajić Jaroslava V. (Food and Feed Research)
Dandelion (Taraxacum officinale L.) has a long history in traditional herbalism worldwide. Described as non-toxic, the herb has been consumed in various forms as a valuable source of nutrients, minerals and vitamins, the consumption of which may help prevent or reduce the risk of complex diseases such as cancer, obesity, arthritis, hepatitis, cardiovascular and gastrointestinal disorders. All parts of the dandelion herb are edible and contain flavonoids, phenolic acids, alkaloids and terpenes, with the best-studied extracts being from leaves and roots. The most abundant phenolic acids are hydroxycinnamic acid derivatives, especially chicoric acid, chlorogenic acid and caffeic acid. Luteolin and its glucosides are more abundant in extracts from dandelion leaves and flowers. This study aimed to investigate the influence of temperature of subcritical water extraction of dandelion flowers in the interval of 110-160 ° C. The parameters analysed were total phenolic content (TPC), total flavonoid content (TFC), total antioxidant capacity (TAC) and the DPPH radical scavenging activity, determined by UV-spectrophotometry. The highest TPC (36.37 mg GAE/g DW) and TAC (76.80 mg AAE/g DW) were noted in extracts obtained at 140 ° C, while the highest TFC of 10.95 mg RE/g DW was observed when extraction was performed at 130 ° C. As for DPPH scavenging activity, the highest value was for the extraction temperature of 110 ° C (0.906 mg AAE/g DW), and the lowest for the extract obtained at 160° C (0.718 mg AAE/g DW). The results of this study suggest that dandelion flower extracts obtained at moderate temperatures (130-140 ° C) with subcritical water have the highest polyphenol content and antioxidant activity.